World Film Locations. - Block, Marcelline (Intellect Books - World Film Locations Ser., 2014)
Founded by the Puritans in 1630 and the site of many of the American Revolution's major precursors and events (including the Boston Massacre, the Boston Tea Party, and Paul Revere's midnight ride, among others), Boston has played-and continues to play-an influential role in the shaping of the historic, intellectual, cultural, and political landscapes of the United States.